Highway engineering - Rogers, Martin
The repair, renovation and replacement of highway infrastructure, along with the provision of new highways, is a core element of civil engineering, so this book covers basic theory and practice in sufficient depth to provide a solid grounding to students of civil engineering and trainee practitioners. Highway Engineering covers all the basic materials needed by civil engineers to address the analysis, design and construction of motorways and roads. The repair, renovation and replacement of highway infrastructure, along with the provision of new highways, are core elements of civil engineering, so the book covers both theory and practice in sufficient depth to provide a solid grounding to students of civil engineering and trainee practitioners. By making frequent reference to the Department for Transport's Design Manual for Roads and Bridges, Highway Engineering moves in a logical sequence from the planning and economic justification for a highway, to the geometric design and traffic analysis of highway links and intersections, to the design and maintenance of both flexible and rigid pavements. It also places the provision of roads and motorways in context by introducing the economic, political, social and administrative dimensions of the subject, along with introducing the important topic of sustainability in transport engineering. Primarily a text for undergraduate students of civil engineering, the third edition of Highway Engineering covers topics that will also be of interest to surveyors and transport planners. --Book Jacket